Analisis Geokimia Batugamping Daerah Desa Binuang Kecamatan Balusu Kabupaten Barru Provinsi Sulawesi Selatan - Harwan, Harwan; Hafsyam, Muhammad; Juradi, Muhammad Idris (CV Insight Publisher, 2023)
Limestone is a type of sedimentary rock with the main mineral composition being calcite with the chemical formula CaCO3. Limestone found in nature is generally yellowish white, white, gray and black. This research aims to determine the geochemical characteristics of limestone in Binuang Village, Balusu District, Barru Regency and what the chemical composition of limestone in Binuang Village, Balusu District, Barru Regency. The research method uses XRD analysis and XRF analysis methods. in mineralogical analysis using the X-Ray Diffraction method, all limestone samples in 4 stations in the Binuang Village area were composed of minerals such as Calcite (CaCO3) containing 100% calcite. Based on the results of analysis using the X-Ray fluorescence method, all limestone samples at 4 stations showed CaO element values of 52.7-55.4%, LOl of 39.2-43.6%, Fe2O3 of 1.4-2.53 %, MgO is 1.17-1.29%, as well as several other compounds whose percentage is below 1% such as P2O5, SiO2, Al2O3, MnO, K2O, Na2O and TiO2. So the limestone in this study can be categorized as high quality (high grade limestone) because it has a CaO content of > 49%. This means that the limestone samples found in the Binuang Village area, Barru District, South Sulawesi Province have met good quality standards for raw materials for making cement and can be used as an addition in the steel smelting process.